Oxygen-free copper sheet for DBC ceramic copper-clad plate as well as preparation method and application of oxygen-free copper sheet
Through hot rolling and multiple cold rolling + bright annealing treatment, oxygen-free copper sheets were prepared, which solved the problem of unstable grain size after high-temperature welding in the existing technology, and achieved efficient production of DBC ceramic copper clad plates to ensure that Conductivity and welding qualification rate.
Patent Information
- Application Number
- CN202411263872.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to prepare oxygen-free copper sheets that meet the production needs of DBC ceramic copper clad plates, especially in terms of grain size control and conductivity after high-temperature welding.
The method of cold rolling and bright annealing after hot rolling is adopted to control the high-temperature welding grain stability of the copper sheet. The obtained oxygen-free copper sheet does not grow significantly after the welding process between 1065-1085℃. The average grain is about 90μm, meeting the production needs of DBC ceramic copper clad plate.
The stable control of grain size after welding at 1065-1085℃ is achieved. The Vickers hardness is within 108Hv, the conductivity can reach 101% IACS, and the welding qualification rate reaches 100%, meeting the production demand of DBC ceramic copper clad plate.
Smart Images

Figure BDA0005036585180000091 
Figure BDA0005036585180000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic surface metallization, and relates to an oxygen-free copper sheet for a DBC ceramic copper-clad plate, and a preparation method and application thereof. Background Art
[0002] DBC ceramic copper clad laminate is a composite substrate made by directly welding and bonding copper sheets to ceramic substrates such as Al2O3 or AlN at a high temperature of 1065-1085°C. It has the characteristics of high thermal conductivity, high electrical insulation, high mechanical strength, low expansion of ceramics, and high electrical conductivity and excellent welding performance of oxygen-free copper.
[0003] The widely used direct copper-clad ceramic substrate is prepared by eutectic bonding. There is no bonding material between copper and ceramic. During high-temperature service, large thermal stress is often generated due to the large difference in thermal expansion coefficient between copper and ceramic, resulting in the copper layer peeling off from the ceramic surface. Therefore, it has special requirements for the oxygen-free copper sheet used for welding: purity reaches 4N (99.99%), oxygen content <5ppm, Vickers hardness (100-120Hv), conductivity ≥100%IACS, especially for the grains after high-temperature welding, and the grains after welding need to be <150μm.
[0004] CN116042983A discloses a method for preparing a copper plate for a ceramic copper-clad laminate, wherein the copper plate raw material is first subjected to microalloy smelting and cast into a copper ingot, then hot-rolled and milled, and then rough-rolled and annealed and then fine-rolled to obtain a fine-rolled copper plate, and the fine-rolled copper plate is annealed, and multiple rolling and cycle annealing are performed to finally obtain the copper plate. The copper plate raw material needs to be microalloyed, with 60-80ppm calcium, 50-60ppm magnesium, and 20-30ppm molybdenum, and the total impurity content exceeds 100ppm, and the purity cannot meet the 4N requirement, so this method is not suitable for copper sheet processing of DBC ceramic copper-clad laminates.
[0005] CN106216423A discloses a production process of a highly conductive oxygen-free copper strip for a ceramic copper-clad substrate, which comprises the steps of high-purity copper melting and casting, upward continuous casting of copper rods, continuous extrusion, cold rolling, annealing, cold rolling, straightening, cleaning and passivation, slitting, etc. The highly conductive oxygen-free copper strip for a ceramic copper-clad substrate is obtained, but it does not contain the grain size information after the copper strip is bonded to the ceramic substrate at high temperature, and cannot be directly used for DBC ceramic copper-clad substrates.
[0006] The copper sheet obtained by the above scheme cannot meet the production requirements of DBC ceramic copper clad laminates. Therefore, it is very necessary to develop an oxygen-free copper sheet that meets the production requirements of DBC ceramic copper clad laminates. Summary of the invention
[0007] The object of the present invention is to provide an oxygen-free copper sheet for DBC ceramic copper-clad laminates, and a preparation method and application thereof. The oxygen-free copper sheet for DBC ceramic copper-clad laminates prepared by the method of the present invention has no obvious grain growth after the DBC welding process at 1065-1085°C, and the average grain size is about 90μm, which meets the production requirements of DBC ceramic copper-clad laminates.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing an oxygen-free copper sheet for a DBC ceramic copper-clad laminate, the preparation method comprising the following steps:
[0010] (1) hot rolling the copper ingot to obtain a billet;
[0011] (2) cold rolling the blank and then performing bright annealing treatment, and then performing finish rolling treatment to obtain the oxygen-free copper sheet for DBC ceramic copper-clad laminate;
[0012] Wherein, in step (2), the number of times the blank is subjected to bright annealing treatment after cold rolling is ≥3 times.
[0013] The oxygen-free copper sheet of the present invention is limited to the shape of the prepared material, as long as it is in sheet form, it can also be a sheet material such as a copper plate or copper foil.
[0014] In the preparation process of the oxygen-free copper sheet for DBC ceramic copper-clad laminates, at least three cold rolling + bright annealing processes are performed after hot rolling to control the high-temperature welding grain stability of the copper sheet. The grain growth of the prepared copper sheet is not obvious after the DBC welding process at 1065-1085° C., and the average grain size is about 90 μm, thereby meeting the production requirements of the DBC ceramic copper-clad laminates.
[0015] Preferably, the oxygen content of the copper ingot in step (1) is less than 5 ppm.
[0016] Preferably, the purity of the copper ingot in step (1) is ≥4N.
[0017] Preferably, the thickness of the copper ingot in step (1) is 80 to 120 mm, for example, 80 mm, 90 mm, 100 mm, 110 mm or 120 mm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0018] Preferably, a preheating treatment is performed before the hot rolling treatment in step (1).
[0019] Preferably, the temperature of the preheat treatment is 500-800°C, for example, 500°C, 550°C, 600°C, 700°C or 800°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the thickness of the blank in step (1) is 11 to 16 mm, for example, 11 mm, 12 mm, 14 mm, 15 mm or 16 mm, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Preferably, the milling process is performed before the cold rolling in step (2).
[0022] Preferably, the single thickness change rate of the cold rolling in step (2) is ≤30%.
[0023] Preferably, the total thickness change rate of the cold rolling in step (2) is 30-50%, for example: 30%, 35%, 40%, 45% or 50%, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] The thickness change rate of the present invention is the ratio of the reduced thickness of the material after cold rolling to the thickness before cold rolling. The thickness of the material before cold rolling is a, the thickness of the material after cold rolling is b, and the thickness change rate is 1-b / a. Taking three cold rollings as an example, the thickness change rate of the first cold rolling is x, the thickness change rate of the second cold rolling is y, and the thickness change rate of the third cold rolling is z. The total thickness change rate of the three cold rollings is m, where m=1-(1-x)×(1-y)×(1-z).
[0025] Preferably, the temperature of the bright annealing treatment in step (2) is 260-600°C, for example, 260°C, 300°C, 400°C, 500°C or 600°C, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0026] Preferably, the single time of the bright annealing treatment is 1 to 5 hours, for example: 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, etc., not limited to the listed values, other values not listed within the numerical range are also applicable.
[0027] In a second aspect, the present invention provides an oxygen-free copper sheet for a DBC ceramic copper-clad laminate, wherein the oxygen-free copper sheet for a DBC ceramic copper-clad laminate is prepared by the preparation method described in the first aspect.
[0028] Preferably, the thickness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate is 0.1-0.6 mm, for example, 0.1 mm, 0.2 mm, 0.4 mm, 0.5 mm or 0.6 mm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0029] Preferably, the hardness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate is 100-120 Hv, for example, 100 Hv, 105 Hv, 110 Hv, 115 Hv or 120 Hv, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the conductivity of the oxygen-free copper sheet used for the DBC ceramic copper-clad laminate is ≥100% IACS.
[0031] In a third aspect, the present invention provides a DBC ceramic copper-clad laminate, wherein the DBC ceramic copper-clad laminate comprises the oxygen-free copper sheet for the DBC ceramic copper-clad laminate as described in the second aspect.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The oxygen-free copper sheet for DBC ceramic copper-clad laminate prepared by the method of the present invention has no obvious grain growth after the DBC welding process at 1065-1085°C, and the average grain size is about 90 μm, which meets the production requirements of DBC ceramic copper-clad laminates.
[0034] (2) The Vickers hardness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate of the present invention is controlled within 108 Hv, the conductivity can reach 101% IACS, the grain size after welding is controlled within 91 μm, and the welding qualification rate can reach 100%. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0036] Example 1
[0037] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0038] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0039] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of each cold rolling is 15%, and the total thickness change rate of the three cold rollings is 38.6%. The temperature of each bright annealing treatment is 500°C and the time is 3h. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0040] Example 2
[0041] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0042] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 80 mm was preheated at 500° C. and then hot-rolled to obtain a billet with a thickness of 11 mm;
[0043] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed four times, wherein the thickness change rate of the first cold rolling is 20%, the thickness change rate of the second cold rolling is 20%, the thickness change rate of the third cold rolling is 10%, the thickness change rate of the fourth cold rolling is 10%, and the total thickness change rate of the four cold rolling is 48.2%. The temperature of each bright annealing treatment is 550°C and the time is 5h. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0044] Example 3
[0045] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0046] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 120 mm was preheated at 800° C. and then hot-rolled to obtain a billet with a thickness of 16 mm;
[0047] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of the first cold rolling is 30%, the thickness change rate of the second cold rolling is 20%, the thickness change rate of the third cold rolling is 10%, and the total thickness change rate of the three cold rollings is 49.6%. The temperature of each bright annealing treatment is 600°C and the time is 1 hour. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0048] Example 4
[0049] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0050] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0051] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of each cold rolling is 30%, and the total thickness change rate of the three cold rollings is 65.7%. The temperature of each bright annealing treatment is 400°C and the time is 3h. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0052] Example 5
[0053] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0054] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0055] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of each cold rolling is 10%, and the total thickness change rate of the three cold rollings is 27.1%. The temperature of each bright annealing treatment is 400°C and the time is 3 hours. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0056] Example 6
[0057] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0058] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0059] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of each cold rolling is 15%, and the total thickness change rate of the three cold rollings is 38.6%. The temperature of each bright annealing treatment is 250°C and the time is 3h. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by finish rolling.
[0060] Example 7
[0061] This embodiment provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0062] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0063] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + bright annealed three times, wherein the thickness change rate of each cold rolling is 15%, and the total thickness change rate of the three cold rollings is 38.6%. The temperature of each bright annealing treatment is 650°C and the time is 3h. Finally, the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0064] Comparative Example 1
[0065] This comparative example provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0066] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0067] (2) The hot-rolled blank is milled to remove the surface oxide layer and cracks, and then bright annealed at a temperature of 400° C. for 3 h. Finally, the blank is finely rolled to obtain the oxygen-free copper sheet for the DBC ceramic copper-clad laminate.
[0068] Comparative Example 2
[0069] This comparative example provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0070] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0071] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then subjected to secondary cold rolling + bright annealing, wherein the thickness change rate of each cold rolling is 20%, the total thickness change rate of the secondary cold rolling is 36%, the temperature of each bright annealing is 400°C, the time is 3h, and finally the oxygen-free copper sheet for DBC ceramic copper clad laminate is obtained by fine rolling.
[0072] Comparative Example 3
[0073] This comparative example provides an oxygen-free copper sheet for DBC ceramic copper-clad laminate, and the preparation method of the oxygen-free copper sheet for DBC ceramic copper-clad laminate is as follows:
[0074] (1) An oxygen-free copper ingot with a purity of 4N, an oxygen content of less than 5 ppm, and a thickness of 100 mm was preheated at 600° C. and then hot-rolled to obtain a billet with a thickness of 14 mm;
[0075] (2) The blank obtained by hot rolling is milled to remove the surface oxide layer and cracks, and then cold rolled + low-temperature annealing is performed three times, wherein the thickness change rate of each cold rolling is 15%, and the total thickness change rate of the three cold rollings is 38.6%. The temperature of the low-temperature annealing treatment is 200°C and the time is 6 hours. Finally, the oxygen-free copper sheet for the DBC ceramic copper-clad laminate is obtained by fine rolling.
[0076] Performance Test:
[0077] The hardness of the oxygen-free copper sheets prepared in the embodiment and the comparative example was tested using a Vickers hardness tester, the conductivity of the oxygen-free copper sheets was tested using a conductivity meter, the grain size of the ceramic copper-clad laminate after welding was measured using a metallographic microscope, and the welding pass rate of the ceramic copper-clad laminate was tested using C-Scan. The test results are shown in Table 1:
[0078] Table 1
[0079]
[0080]
[0081] As can be seen from Table 1, from Examples 1-3, the Vickers hardness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate of the present invention is controlled within 108 Hv, the conductivity can reach 101% IACS, the grain size after welding is controlled within 91 μm, and the welding qualification rate can reach 100%.
[0082] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the oxygen-free copper sheet for DBC ceramic copper clad laminates described in the present invention, the thickness change rate of each cold rolling and the total thickness change rate of cold rolling will affect the effect of obtaining the oxygen-free copper sheet for DBC ceramic copper clad laminates. When the thickness change rate of each cold rolling is controlled within 30% and the total thickness change rate of cold rolling is controlled within 30-50%, the effect of obtaining the oxygen-free copper sheet for DBC ceramic copper clad laminates is better. If it exceeds the above range, the grain size after welding is likely to be too large.
[0083] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the oxygen-free copper sheet for DBC ceramic copper clad laminates of the present invention, the temperature of the bright annealing treatment will affect the effect of the oxygen-free copper sheet for DBC ceramic copper clad laminates. The temperature of the bright annealing treatment is controlled at 260-600°C, and the effect of the oxygen-free copper sheet for DBC ceramic copper clad laminates is better. If the temperature of the bright annealing treatment is too low, the hardness of the oxygen-free copper sheet for DBC ceramic copper clad laminates is too high. If the temperature of the bright annealing treatment is too high, the grains are likely to be too large after welding.
[0084] By comparing Example 1 with Comparative Example 1, it can be seen that if cold rolling is not performed after the milling process, the grain size after welding cannot meet the requirements.
[0085] By comparing Example 1 and Comparative Example 2, it can be seen that the present invention performs at least three cold rolling + bright annealing treatments to control the grains to an appropriate size. If the number of cold rolling + bright annealing treatments is too small, the grains are likely to be too large and cannot meet the requirements.
[0086] From the comparison between Example 1 and Comparative Example 3, it can be seen that conventional low-temperature annealing after cold rolling easily leads to high hardness and easy oxidation of the surface, requiring additional cleaning.
[0087] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an oxygen-free copper sheet for a DBC ceramic copper-clad laminate, characterized in that: The preparation method comprises the following steps: (1) hot rolling the copper ingot to obtain a billet; (2) cold rolling the blank and then performing bright annealing treatment, and then performing finish rolling treatment to obtain the oxygen-free copper sheet for DBC ceramic copper-clad laminate; Wherein, in step (2), the number of times the blank is subjected to bright annealing treatment after cold rolling is ≥3 times.
2. The preparation method according to claim 1, characterized in that The oxygen content of the copper ingot in step (1) is less than 5 ppm; Preferably, the purity of the copper ingot in step (1) is ≥4N; Preferably, the thickness of the copper ingot in step (1) is 80 to 120 mm.
3. The preparation method according to claim 1 or 2, characterized in that: Preheating is performed before the hot rolling process in step (1); Preferably, the preheating temperature is 500-800°C.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The thickness of the blank in step (1) is 11 to 16 mm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (2) performs milling treatment before cold rolling.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The single thickness change rate of the cold rolling in step (2) is ≤30%; Preferably, the total thickness change rate of the cold rolling in step (2) is 30-50%.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the bright annealing treatment in step (2) is 260-600° C. Preferably, the single bright annealing treatment time in step (2) is 1 to 5 hours.
8. An oxygen-free copper sheet for DBC ceramic copper-clad laminate, characterized in that: The oxygen-free copper sheet for DBC ceramic copper-clad laminate is prepared by the preparation method according to any one of claims 1 to 7.
9. The oxygen-free copper sheet for DBC ceramic copper-clad laminate according to claim 8, characterized in that: The thickness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate is 0.1 to 0.6 mm; Preferably, the hardness of the oxygen-free copper sheet for the DBC ceramic copper-clad laminate is 100-120 Hv; Preferably, the conductivity of the oxygen-free copper sheet used for the DBC ceramic copper-clad laminate is ≥100% IACS.
10. A DBC ceramic copper-clad laminate, characterized in that: The DBC ceramic copper-clad laminate comprises the oxygen-free copper sheet for DBC ceramic copper-clad laminate according to claim 8 or 9.
Citation Information
Patent Citations
Production technology of high-conductivity oxygen-free copper strip for ceramic copper-clad laminate
CN106216423A
Cited By
Copper plate as well as preparation method and application thereof
CN121951273A
